HUKUM PENGGUNAAN DANA TBDSP UNTUK PEMBIAYAAN OPERASIONAL BANK SYARIAH DALAM PERSPEKTIF FATWA MUI NO.123/DSN-MUI/XI/2018 (STUDI KASUS BANK SUMUT SYARIAH KCP MARELAN RAYA) - Abdan Taqyanto; Fatimah Zahara (Jurnal Akuntansi dan Pajak, 2023)
The purpose of this study is to find out the legal use of TBDSP funds for financing Bank Sumut Syariah Kcp Marelan Raya in the perspective of MUI Fatwa No.123/DSN-MUI/XI/2018. This investigation makes use of qualitative data and methods for describing phenomena. In this investigation, we combined data from both primary and secondary sources. Methods of gathering information via direct observation, interviews, and written records. According to the findings of this research, TBDSP money is used in a used for benevolence funds and bank operational financing. Bank of North Sumatra does not have a special storage for current accounts or deposits, and non-halal TBDSP funds. The special shelter for funds is only income from financing customer fines that are used for policy funds. Meanwhile, the income from the funds channeled to financing is used for the operations of the Islamic Bank of North Sumatra. The law on the use of TBDSP funds for operational financing of Islamic banks if it is associated with MUI Fatwa No. 123/DSN-MUI/XI/2018 this is not in accordance with the fatwa because the Islamic banks of North Sumatra still use these funds for benevolence funds and operational financing of Islamic banks. Keywords: Law, TBDSP Fund, Sharia Bank Operations, MUI Fatwa